Visual thinking : empowering people & organizations through visual collaboration - Brand, Willemien, ....-; Koene, Pieter, ....-; Ars, Martijn, ....-; Verheijen, Pieter, ....- (Amsterdam : BIS publishers, 2017)
Visual thinking and drawing are both becoming increasingly important in today's business settings. A picture really can tell a thousand words. Visualization is a crucial part of the journey for companies seeking to boost enterprise agility, break down silos and increase employee and customer engagement. Visualizing thought processes can help break down complex problems. It empowers teams and staff to build on one another's ideas, fosters collaboration, jump-starts co-creation and boosts innovation. This book will help brush aside misconceptions that may have prevented you using these techniques in your workplace. You don't need Van Gogh's artistic talent or Einstein's intelligence to harnass the power of visual thinking and make your company more successful.
Keywords: Visueel denken